Hubungan kejadian malaria pada ibu hamil dengan BBLR di Puskesmas Nangapanda tahun 2011 - Emiliana Beti Sophian; Dwiana Estiwidani; Sumarah Sumarah (Poltekkes Kemenkes Yogyakarta, 2013)
Neonatal Mortality rate in Indonesia on 2010 were 19 per 1000 live births. Neonatal mortality rate in the province of south east Nusa east (NTT) on 2010 were 853 or 9,34 per 1 ,000 live births caused by death due to asphyxia of 37,9%, followed by Low Birth Weight (LBW) are 28,1% after caused are 28% and infection 3 cases (0,35%). One of maternal factors which influenced, LBW is malaria. Ende regency is the third highest incidence of malaria in the province of NTT 2011 by 28.89%. Purpose: to know correlation of malaria with LBW. Methods: This study use an observational study with case-control design, using sampling technique purposive with sample 53 case and 53 controls. Analysis used univariate, bivariate by chi-square. Result: The results of chi square test p-value of 0.001, which means there is a correlation of malaria and LBW. Results of statistical analysis showed that OR= 3.827 Cl (95%) 1,653-8,859 means that malaria has 3.8 times higher probability than LBW compared with those not exposed to malaria. maternal malaria, birth weight